The Effect Of Playing Collage On Fine Motor Abilities In Children Aged 4-6 Years - indah wahyuningsih; Rosyidah Alfitri (Universitas Prima Indonesia, 2026)
Fine motor skills are a crucial aspect of early childhood development because they influence a child's ability to perform various daily activities and their readiness to learn. One activity that can stimulate fine motor development is collage play. This study aimed to determine the effect of collage play on fine motor skills in children aged 4–6 years at Bunga Tanjung Banjararum Preschool. This study used a pre-experimental design with a one-group pretest-posttest design. The sample consisted of 20 children aged 4–6 years selected using a purposive sampling technique. The children's fine motor skills were measured before and after the college play intervention. The data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed an increase in fine motor skills after the collage play intervention. Before the intervention, most children were in the moderate fine motor skills category, while after the intervention, most were in the good fine motor skills category. The statistical analysis using the Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of college play on the fine motor skills of children aged 4–6 years. The conclusion of this study is that collage play effectively improves fine motor skills in children aged 4–6 years at Bunga Tanjung Banjararum Preschool.